PENGARUH PROMO GRATIS ONGKIR DAN CUSTOMER EXPERIENCE TERHADAP KEPUASAN PELANGGAN PENGGUNA APLIKASI SHOPEE - Rinanda Hamida Lubis; Zein Ramadhan; Abdul Yusuf (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2021)
This study aims to determine the effect of free shipping promos and customer experience on customer satisfaction. The population in this study are customers who shop online through the Shopee application. The technique used in sampling is non-probability sampling with purposive sampling method. The sample in this study amounted to 100 respondents. Data collection was obtained from distributing questionnaires and literature studies. The data analysis method used in this research is multiple linear regression. The results showed that the free shipping promo and customer experience had a positive and significant effect on customer satisfaction. Based on the results of the coefficient of determination test, the R Square value of the customer experience variable is 0.384 or 38.4%, meaning that the customer experience variable has the most dominant influence on customer satisfaction.